Analisis Keterampilan Menulis Surat Pribadi Bahasa Jerman - Arsyad, Finastika Arya Putra; Anwar, Muh; Mannahali, Misnah (Universitas Negeri Makassar, 2025)
Abstract. This research aims to determine the level of German personal letter writing skills of class XII IPS students at SMA Negeri 1 Maros. This research applies a quantitative descriptive method using a research instrument in the form of a personal letter writing test in German. The population in this study was students of class XII IPS SMA Negeri 1 Maros with a total of 133 students and 23 students were selected from class This research uses the Purposive Sampling method, namely selecting research samples for certain reasons. This research describes the results of the analysis of personal letter writing skills in German for class XII IPS students at SMA Negeri 1 Maros which reached 62.71% or was included in the sufficient categoryKeywords: Writing skills, personal letters, German Language